Jamaica Kincaid's Writings of History A Poetics of Impermanence - Purk, Antonia (American Frictions, 2023)
Jamaica Kincaid's works consistently explore the long-lasting effects of colonial history on contemporary lives. Focusing on the media of text, image, and the human body, the chapters of this book show how Kincaid's ''poetics of impermanence'' destabilize hegemonial representations of history and in their stead establish self-determined versions of the past through a multiplication of perspectives and voices.